Endoscopic application of hemostatic thrombin-gelatin matrix (FloSeal) in anticoagulated pigs - Hammes, Christoph; Moersdorf, G.; Refeidi, A.; Post, Stefan; Kähler, Georg (Minimally invasive therapy & allied technologies, 2010)
Flexible endoscopy is the method of choice for the diagnosis and therapy of upper gastrointestinal bleeding, but there are still problems during therapy of patients with coagulation disorders. FloSeal® is a hemostatic matrix largely independent of the body's own clotting system. A newly developed endoscopic applicator for FloSeal® was tested in a survival study on pigs with impaired clotting. In a total of eight pigs ulcerous lesions Forrest Ib were induced and the bleeding stopped by applying FloSeal®. Thirty minutes before intervention six pigs were given full weight-adjusted heparinization or a maximum dose of ASS in advance. The Hb course was monitored over the next 48 hours and a postmortem examination was performed. In each case, FloSeal® was successfully applied and all bleedings could be stopped. In both groups (except the control group) spontaneous extraintestinal bleeding occurred, but in only one case in the ASS group a gastrointestinal bleeding happened. The Hb course was stable in all other animals. FloSeal® can also be used endoscopically using the applicator being presented here for the first time. It is suited for primary hemostasis of excavated sources of bleeding especially in situations where coagulation is impaired.
Gesehen am 08.03.2023